Analisis Efektivitas Realisasi Penerimaan Zakat, Infaq dan Sedekah (ZIS) Badan Baitul Mal Kota Langsa - Yenni Samri Juliati Nasution; Agustina Nurul Fajriah; Azhar, Iqlima; Nasrul Kahfi Lubis (Jurnal Penelitian Ekonomi Akuntansi, 2025)
This research aims to determine the effectiveness and growth of Zakat, infaq and Shodaqah collected by Baitul mal Langsa City. This research uses secondary data from the 2014-2023 Langsa City Regional Government Financial Report, with a quantitative approach and analyzed descriptively. The results of this research found that the collection of Zakat, Infaq and Shodaqah for nine years in Langsa City was effective in 2014-2022, and in 2023 Zakai, infaq and shodaqah collection will not be effective. On average, Ziswaf's budget growth for the 2014-2023 period is 19%. Ziswaf realization growth averaged 13%. Ziswaf's budget growth and realization during 2014-2023 could not be balanced with growth in realization. This research analyzes descriptively using secondary data obtained from the Langsa City Baitul Mal Agency so that the specific research results still have not solved the problem regarding the ineffectiveness of ZISWAF growth, so it is recommended for further research to use a questionnaire as an analysis tool that is distributed to related parties managing ZISWAF.